Seismic vulnerability assessment for the historical areas of the Timisoara city, Romania. (July 2019) - Mosoarca, Marius; Onescu, Iasmina; Onescu, Eugen; Azap, Bianca; Chieffo, Nicola; Szitar-Sirbu, Mirela
Abstract: Romania is an eastern European country, with two major seismic zones, Vrancea and Banat. Timisoara is the most important city located in the Banat seismic area, characterized by shallow earthquakes. The city with its many architectural values was declared the European Capital of Culture for 2021. Obviously, an important number of activities that will take part in 2021 will be held in the historical zones of Timisoara, which are also expected to be the most visited ones. In order to assure both the safety of Timisoara's citizens and of the tourists is very important to acknowledge the seismic vulnerability of the buildings of these historical areas. This article presents a study in which there was investigated the seismic vulnerability of 25 buildings from two historic areas, Fabric and Iosefin which were classified according to their geometrical and structural characteristics. There was determined the seismic vulnerability for different scenarios depending on the EMS-98 macroseismic intensity for each identified typology, considered with the representative geometrical and the structural configurations for the zone. The vulnerabilities were obtained using the quick vulnerability assessment methodology, i.e.: the Vulnerability Index Method and the mechanical methodology based on the pushover analysis obtained with the Tremuri software. For the first time in Timisoara, there were shaped both the vulnerability and fragility curves of the buildings under analysis. This study also proposes a new methodology which also takes into consideration the influence of the cultural value in the process of assessing the seismic vulnerability. It is based on the original vulnerability form of the Vulnerability Index Method and on the correlation law between all these methods and it represents the first step of a larger seismic vulnerability assessment for the Timisoara city. Highlights: the empirical seismic vulnerability assessment is applied at urban scale, for >100 historical buildings a new seismic vulnerability assessment methodology is proposed considering the cultural value of the buildings the results of 3 different methodologies are compared and a direct correlation between them is proposed damage scenario is presented for macroseismic intensity VII EMS-98 for two historical areas in Timisoara, Romania consideration of cultural value in the seismic vulnerability assessment improves the importance of historical buildings